Penggunaan Metode Inquiry untuk Meningkatkan Hasil Belajar IPS Siswa Kelas IV SD Inpres Lansot - Jovanka M. Wua; Widdy H.F. Rorimpandey; Margareta O. Sumilat (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to improve social studies learning outcomes through the use of the Inquiry Method for Grade IV Students of SD Inpres Lansot. The method used in this research is Classroom Action Research (CAR), using the spiral model from Kemmis and Mc Taggart with four stages: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The subjects of this study were fourth-grade students at SD Inpres Lansot. The data collection technique used in this research is the observation technique (observation and test). While the data obtained were analyzed by calculating the percentage and average student learning outcomes. The results showed that the achievement of learning outcomes in the first cycle was 70%, in the second cycle it increased to 84%. Thus the use of the inquiry method can improve social studies learning outcomes fourth-graduate students of SD Inpres Lansot